Algal Autophagy Is Necessary for the Regulation of Carbon Metabolism Under Nutrient Deficiency - Kajikawa, Masataka; Fukuzawa, Hideya (Frontiers in Plant Science, 2020)
Autophagy is a mechanism to recycle intracellular constituents such as amino acids and other carbon- and nitrogen (N)-containing compounds. Although autophagy-related (ATG) genes required for autophagy are encoded by many algal genomes, their functional importance in microalgae in nutrient-deficiency has not been appraised using ATG-defective mutants. Recently, by characterization of an insertional mutant of the ATG8 encoding a ubiquitin-like protein indispensable for autophagosome formation in a green alga Chlamydomonas reinhardtii, we have provided evidence that supports the following notions. ATG8 protein is required for the degradation of lipid droplets and triacylglycerol (TAG) triggered by resupply of N to cell culture in N-deficient conditions. ATG8 protein is also necessary for starch accumulation under phosphorus-deficient conditions. Algal autophagy is not necessary for inheritance of chloroplast and mitochondrial genomes. In this review, we discuss the physiological roles of algal autophagy associated with nutrient deficiency revealed by the genetic and biochemical analyses using disruption mutants and reagents that inhibit the fatty acid biosynthesis and vacuolar H+-ATPase.